Pattern of Neurological Improvements in Patient with Lumbar Disc Herniation after Microdiscectomy: Experience at the Fourth Oldest Western Medical Facility in South Asia - Niraula, Kiran; Irfan, Muhammad; Limbu, Chandra P; KC, Raj Kumar; Shaheen, Muhammad A; Ghimire, Megha (Nepal Journal of Neuroscience, 2017)
The pattern of improvement in Neurological status after disc surgery is different. The chronology of improvement in Medical Research Council (MRC) scores, sensory status and improvement in Straight Leg Raise (SLR) test degrees is beneficial in management part to surgeons, relatives and the patients. To assess pattern of neurological outcomes in patients with lumbar disc herniation after microdiscectomy in terms of muscle power, sensory status and SLR. A Quasi experimental study comprising 70 consecutive cases though non-probability purposive sampling technique of both the sexes admitted in Neurosurgery department, Mayo Hospital operated for the 1st time for any disc pathology with no other spinal lesions giving consent themselves or though legal guardians was conducted. Pain for leg and back was measured pre and post-operatively was done by VAS which had 42 days of follow up. Standard Neurological examinations were conducted pertaining to muscle power (by MRC), sensory status and SLR test pre and post-operatively. Variables according to their nature were expressed in the form of Mean±SD, Median (Range) and Frequency (percentage). Mc Neumer’s chi square test and paired t test were used to see association between preoperative and post-operative Neurological status depending on their nature viz: qualitative or quantitative respectively in SPSS version 15. Out of 70 patients 74% were male and 26% were females. Mean±SD of patients was 37.6±13.0 years. Majority were Laborers after housewives. Illiterates, Poor lifting techniques were the most common characteristics in the respective headings of education and employment. Most common level of disc herniation was L4-L5, L5- S1 level (96%) where Prolapse and extrusion were most common MRI findings. As compared to pre-operative (3.4) muscle power 1st and 42nd day power were respectively 4.0 and 4.7 (p=0.001). Pre-operatively only 32 (45.7%) had normal sensation which improved to 38 (54.3%) and 51 (72.9%) respectively in 1st and 42nd day of surgery (p=0.001). Pre-operative mean SLR improved to 98.6 degrees in 1st POD and continued to be the same till 42nd day (p=0.001). All the MRC findings, sensory status and SLR values in each post-operative days were statistically significant with the baseline by paired t test (p=0.001). MRC and Sensory status had same pattern of improvement (r=0.0. p=0.04) unlike SLR which total improvements were see in 1st POD itself. In conclusion, muscle power and sensory improvement follows same improvement pattern whereas maximum SLR improves in the 1st POD itself. Nepal Journal of Neuroscience, Vol. 14, No. 2, 2017 Page: 8-15